Evaluation of three radiographic methods (conventional periapical, digital periapical and panoramic) in the diagnosis of artificially produced periapical lesions (Pesquisa Odontológica Brasileira, 2001)
This research was carried out in order to evaluate three radiographic methods - conventional periapical, digital periapical and panoramic - in the diagnosis of artificially produced periapical lesions. For this purpose, 5 mandibles, with lesions produced by means of spherical drills of different sizes, were used. The research was divided into five distinct phases, as follows: phase Z (initial) - characterized by the absence of lesion; phase R - lesion produced with a number 6 drill; phase J - lesion produced with a number 8 drill; phase D - lesion produced with a number 10 drill; and phase H - lesion reaching the vestibular cortex. The lesions were produced in quadrants. Radiographs were made after each phase and analyzed by 4 experts in radiology. For the digital system there was statistically significant difference in phase R (in the region of incisors) and in phase H (in the region of premolars). In the region of molars there was statistically significant difference in phase D for panoramic radiography. It must be pointed out that panoramic radiography produced the less effective results in phase H.